2013
DOI: 10.1002/mus.23722
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor polyneuropathy in patients with SMA type‐1: Electroneuromyographic findings

Abstract: Survival motor neuron 1 (SMN1) gene analysis should be considered if clinical features are consistent with SMA, even if pathological or electrophysiological findings demonstrate peripheral sensorimotor polyneuropathies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 19 publications
(55 reference statements)
4
16
0
Order By: Relevance
“…Importantly, sensory pathology in SMA patients is becoming increasingly well characterized ( Supplementary Table 2 ). Several reports of patients with SMA type 1 indicate abnormal sensory conduction ( Duman et al , 2013 ) or absence of sensory responses ( Reid et al , 2016 ), as well as axonal degeneration in sensory nerves ( Rudnik-Schoneborn et al , 2003 ). In earlier studies of presumed SMA cases, axonal degeneration of sensory neurons was also identified, alongside ballooned neurons and chromatolysis within DRGs ( Marshall and Duchen, 1975 ; Carpenter et al , 1978 ; Murayama et al , 1991 ).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, sensory pathology in SMA patients is becoming increasingly well characterized ( Supplementary Table 2 ). Several reports of patients with SMA type 1 indicate abnormal sensory conduction ( Duman et al , 2013 ) or absence of sensory responses ( Reid et al , 2016 ), as well as axonal degeneration in sensory nerves ( Rudnik-Schoneborn et al , 2003 ). In earlier studies of presumed SMA cases, axonal degeneration of sensory neurons was also identified, alongside ballooned neurons and chromatolysis within DRGs ( Marshall and Duchen, 1975 ; Carpenter et al , 1978 ; Murayama et al , 1991 ).…”
Section: Discussionmentioning
confidence: 99%
“…Electrodiagnostic studies show variable features of motor neuron/axon loss consistent with loss of motor neuron function . Sensory involvement is usually lacking, but exceptional cases have been reported with associated sensory neuropathy or sensory ganglionopathy . Electrodiagnosis remains an important diagnostic tool in atypical cases and non–5q‐related SMA to demonstrate the neurogenic nature of the illness.…”
Section: Other Testing Modalitiesmentioning
confidence: 99%
“…For example, it is now known that multiple different organ systems and cell types are affected in SMA (Nash et al, 2016), including defects in the heart, vasculature and skeletal muscles (Hamilton and Gillingwater, 2013; Shababi et al, 2014). Alongside these systemic pathologies, defects in sensory neurons have been reported in SMA patients, including abnormal sensory conduction (Duman et al, 2013; Yonekawa et al, 2013) or complete absence of sensory nerve action potentials (Yuan and Jiang, 2015; Reid et al, 2016), along with axonal degeneration and loss of myelinated fibers within sensory nerves (Korinthenberg et al, 1997; Omran et al, 1998; Rudnik-Schoneborn et al, 2003). Depending on the type of SMA, varying structural abnormalities in muscle spindles have been described, although some of these findings are contradictory and would require further investigation (Marshall and Duchen, 1975; Bobele et al, 1996; Kararizou et al, 2006).…”
Section: Sensory-motor Defects In Spinal Muscular Atrophy (Sma)mentioning
confidence: 99%